IMPLEMENTASI KURIKULUM MERDEKA BERORIENTASI LITERASI PROYEK PROFIL PELAJAR PANCASILA UNTUK MENINGKATKAN JIWA NASIONALISME SISWA SD - widiastika, gede; Bayu Ariska Putra Gotama, Putu (Adi Widya: Jurnal Pendidikan Dasar, 2026)
Currently, the world of education is facing a condition where students experience degradation of the values of Pancasila. This is proven by various cases of irregularities such as brawls, bullying, harassment and various other immoral problems. This research aims to analyze the implementation of the project-oriented independent curriculum on the profile of Pancasila students in elementary schools. This study uses a qualitative method. The subjects in this research were school principals, class teachers and elementary school students. The data collection instrument used a cognitive instrument in the form of a questionnaire. Data analysis techniques include data collection, reduction, presentation and conclusions. The results of research on each aspect obtained the following results. 1). The aspect of having faith, being devoted to God Almighty has a score percentage of 86%. 2). The global diversity aspect has a percentage of 82%. 3). The mutual cooperation aspect has a percentage of 80%. 4). The independence aspect has a percentage of 82%. 5). The critical thinking aspect has a percentage of 77%, and 6). The creative aspect has a percentage of 79%. Thus, the implementation of an independent curriculum oriented towards the Pancasila student profile can improve the nationalism of elementary students.